Construction of DNA Vaccine of Extracellular Region of Vascular Endothelial Growth Factor Receptor 2 and Its Antitumor Activity in Vivo - Sang, Yao (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Introduction: it constructed recombinant DNA vaccine of extracellular region of vascular endothelial growth factor receptor 2 (VEGFR2) and analyzed its in vivo activity against H22 transplanted hepatoma. Methods: the gene fragment of VEGFR2 extracellular region 1-3 was amplified, and the pcDNA3.1(+)/exVEGFR2 recombinant plasmid was constructed. The expression of exVEGFR2 was detected by Western blot. Subsequently, liposome (LP) pcDNA3.1(+)/exVEGFR2 complex (LP-pcDNA3.1(+)/exVEGFR2) was prepared and immunized to C57BL/6 mice. The cytotoxic activity mediated by cytotoxic T cells (CTLs) was analyzed by 51Cr release assay. H22 tumor bearing C57BL/6 mouse model was prepared. Quadriceps femoris muscle was injected with normal saline (saline group, AG), LP-pcDNA3.1(+) 100 μL (1 μg/μL, LP-pcDNA3.1(+) group, BG), and LP-pcDNA3.1(+)/exVEGFR2 100 μL (1 μg/μL, LP-pcDNA3.1(+)/exVEGFR2 group, CG). Tumor growth and death were recorded, and microvessel density (MVD) was evaluated by CD31 immunohistochemical staining. Results: a 1252 bp of exVEGFR2 sequence was amplified, and a specific band expressing 44 kDa molecular weight was constructed by transfecting pcDNA3.1(+)/exVEGFR2 into COS-7 cells. After immunizing C57BL/6 mice for 6 weeks, CTLs experiment suggested that LP-pcDNA3.1(+)/exVEGFR2 could effectively mediate the toxic effect of VEGFR2 positive H22 cells. The in vivo antitumor activity experiment found that as against AG and BG, the tumor volume, weight, and MVD were markedly reduced, the tumor latency time was markedly prolonged, and the average survival time was also markedly prolonged in CG (P < 0.05). Conclusion: LP-pcDNA3.1(+)/exVEGFR2 can effectively activate C57BL/6 mice to produce specific anti-VEGFR2 immune response, and then produce anti-tumor cell immunotoxicity in vitro and in vivo. Inhibiting angiogenesis can effectively prolong the survival time of H22 tumor bearing mice.